Analisis Tingkat Minat Belajar Mahasiswa Pendidikan Matematikan pada Matakuliah Kimia Dasar - Idrus, Syarifa Wahidah Al (MASALIQ, 2023)
This study aims to analyze the learning interest of mathematics education study program students in basic chemistry learning. This research is quantitative descriptive. This research was conducted by giving a questionnaire to 33 first semester students of mathematics education study program for the 2022/2023 academic year. The results showed that the learning interest of mathematics education study program students in learning basic chemistry was seen in the four indicators observed. The indicator of interest in the low category is 24%, students who are interested in the medium category are 61% and students who are interested in the high category are 15%. Indicators of attention in the low category are 18%, students who have attention in the moderate category are 70% and attention in the high category is 12%. The involvement indicator shows that the medium and high categories are the same, namely 39% and the rest are in the low category. The indicator of feeling happy in the high category is 9%, the medium category is 75% and the rest is in the low category. For all indicators, the category that dominates is the medium category. The lowest high category is on the indicator of feeling happy, namely 9%.